MOTIVASI MAHASISWI PROGRAM STUDI PENDIDIKAN AGAMA ISLAM FAKULTAS ILMU TARBIYAH DAN KEGURUAN IAIN AMBON DALAM MENGGUNAKAN CADAR - Farhana Fattaroeba; Samad Umarella; Saddam Husein (al-Iltizam: Jurnal Pendidikan Agama Islam, 2021)
This study aims to determine the motivation and factors supporting andinhibiting student motivation in using the veil. The research in this thesis uses a mixedmethod which is a mixed type of research, namely a combination of qualitative andquantitative which produces data in the form of words or sentences and also producesdata in the form of numbers or percentages of the observed subjects. The subjectsstudied were students of the Islamic Religious Education study program, Faculty ofTarbiyah and Teacher Training, IAIN Ambon, which consisted of 12 female students whostill wore the veil. Data collection methods used include interviews, questionnaires anddocumentation. Based on the results of the study found that: The motivation of studentsof the Islamic Education Study Program Faculty of Tarbiyah and Teacher Training IAINAmbon in using the veil is divided into two, namely intrinsic motivation which includes:mastery goals and need for achievement and extrinsic motivation which includes:expectations of authority from family, expectations educational authority, hope fromfriends and fear of failure. The supporting factors, namely: positive support from family,invitations from friends, and often watching studies related to the virtues of using the veil.There are also inhibiting factors, namely: the fear of being ostracized, as well as negativeassumptions from the family regarding the veil, a less supportive living environment.Furthermore, based on the percentage count processed using quantitative analysis, itwas found that the level of motivation of students of the Islamic Religious EducationStudy Program, Faculty of Tarbiyah and Teacher Training, IAIN Ambon, in using the veil,was in the very high category, with a value of 86.17%.